2018
DOI: 10.1094/mpmi-05-17-0121-fi
|View full text |Cite
|
Sign up to set email alerts
|

The Elicitor Protein AsES Induces a Systemic Acquired Resistance Response Accompanied by Systemic Microbursts and Micro–Hypersensitive Responses in Fragaria ananassa

Abstract: The elicitor AsES (Acremonium strictum elicitor subtilisin) is a 34-kDa subtilisin-like protein secreted by the opportunistic fungus Acremonium strictum. AsES activates innate immunity and confers resistance against anthracnose and gray mold diseases in strawberry plants (Fragaria × ananassa Duch.) and the last disease also in Arabidopsis. In the present work, we show that, upon AsES recognition, a cascade of defense responses is activated, including: calcium influx, biphasic oxidative burst (O and HO), hypers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 110 publications
2
23
0
Order By: Relevance
“…This information led us to evaluate the effect of AsES treatment on ROS production. Previously, Hael‐Conrad et al (2017) reported early ROS production a few hours after AsES application (1–12 hpt). In our work, we extended the analysis and found that the oxidative burst presented another peak of H 2 O 2 formation at 2 dpp (48 hpp), also suggesting a biphasic pattern (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This information led us to evaluate the effect of AsES treatment on ROS production. Previously, Hael‐Conrad et al (2017) reported early ROS production a few hours after AsES application (1–12 hpt). In our work, we extended the analysis and found that the oxidative burst presented another peak of H 2 O 2 formation at 2 dpp (48 hpp), also suggesting a biphasic pattern (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…It is worthwhile mentioning that it has been reported that AsES induces the temporal accumulation of salicylic acid (SA) in strawberry plants, and that the accumulation peak occurred at approximately 48 hpp (Hael‐Conrad et al 2017). However, evaluation of the expression of SA‐dependent genes, such as FaPR1 and FaCH2.1 , suggests that the influence of SA would extend to 72 hpp (Chalfoun et al 2013) or even later (Hael‐Conrad et al 2017). This scenario allowed us hypothesize that crosstalk between the SA and ET pathways is taking place, so that when plants are treated with AsES, the first ET production peak takes place when SA has not yet accumulated, and the second peak takes place when the intracellular concentration of SA has decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Biotic elicitors are produced by the attack of pathogens or herbivores [18]. Due to an increase in the demand of food safety and quality, elicitors have been studied as a replacement for some chemical pesticides [19].…”
Section: Introductionmentioning
confidence: 99%
“…Induced resistance implies that plants initiate the immune system with an enhanced defense response when they have failed to defend themselves with constitutive defense mechanisms against biotic or abiotic stresses [5]. The defense responses consists of hypersensitive 2 of 8 response (HR), enhancement of cell wall, accumulation of phytohormones and production of secondary metabolites, leading to toxicity or deterrent against pathogens or herbivores [6,7]. In one study, Bacillus cereus was introduced into tomato plants by seed microbiolization and enhanced tomato plant resistance against Alternaria solani, Phytophthora infestans and Septoria lycopersici [8].…”
Section: Introductionmentioning
confidence: 99%
“…Plant hormones, jasmonic acid, and salicylic acid have been show to induce plant defense responses against pathogens and herbivores [9,10]. Some compounds discovered from plant pathogens were also found to be efficient in triggering plant defense responses and enhanced plant resistance, like PeBA1 (Protein elicitor from Bacillus amyloliquefaciens NC6) and AsES (Acremonium strictum Elicitor Subtilisin) [6,11]. It could be concluded that induced resistance could be employed to control plant pathogens and herbivores in agriculture.…”
Section: Introductionmentioning
confidence: 99%